2023
DOI: 10.1002/adma.202209904
|View full text |Cite
|
Sign up to set email alerts
|

User‐Controlled 4D Biomaterial Degradation with Substrate‐Selective Sortase Transpeptidases for Single‐Cell Biology

Abstract: Stimuli‐responsive biomaterials show great promise for modeling disease dynamics ex vivo with spatiotemporal control over the cellular microenvironment. However, harvesting cells from such materials for downstream analysis without perturbing their state remains an outstanding challenge in 3/4‐dimensional (3D/4D) culture and tissue engineering. In this manuscript, a fully enzymatic strategy for hydrogel degradation that affords spatiotemporal control over cell release while maintaining cytocompatibility is intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…This mode of reactivity potentially has uses in the context of SML technology, where recent work has highlighted the utility of sortase-substrate pairs that offer alternatives to the canonical LPXTG motif. 8,45,46 This work also contributes to the fundamental understanding of substrate recognition by sortases, providing further evidence that sortases within the same class can exhibit significant differences in substrate selectivity. We anticipate that a thorough understanding of these differences, particularly at the structural level, may prove valuable for both the continued development of SML and the design of therapeutics that target sortases in vivo .…”
Section: Discussionmentioning
confidence: 79%
“…This mode of reactivity potentially has uses in the context of SML technology, where recent work has highlighted the utility of sortase-substrate pairs that offer alternatives to the canonical LPXTG motif. 8,45,46 This work also contributes to the fundamental understanding of substrate recognition by sortases, providing further evidence that sortases within the same class can exhibit significant differences in substrate selectivity. We anticipate that a thorough understanding of these differences, particularly at the structural level, may prove valuable for both the continued development of SML and the design of therapeutics that target sortases in vivo .…”
Section: Discussionmentioning
confidence: 79%
“…Nonetheless, this new iEDDA-CSI gelation may benefit light and radical-free hydrogel cross-linking and cell/protein encapsulation. In contrast, the highly tunable and predictable degradation of these hydrogels could be leveraged for autonomous cell/spheroid recovery without using external degradation triggers, such as temperature change or supplying proteases, two common approaches reported in the literature. , In addition, the new iEDDA-CSI assembled and degradable hydrogels may be leveraged for in vivo drug and cell delivery, , since the degradation time is ideal for the stability of protein-based therapeutics which range from days to months in an in vivo setting …”
Section: Resultsmentioning
confidence: 99%
“…Degradation behavior plays an important role in controlling the rate of drug release and achieving tissue regeneration. [ 27 ] Therefore, the in vitro degradation kinetics of the composite hydrogels were studied in phosphate‐buffered saline (PBS) at 37 °C. The in vitro degradation curves showed that the pristine GelMA hydrogels degraded at a faster rate.…”
Section: Resultsmentioning
confidence: 99%